Penyaluran Kredit Cepat Aman (KCA) Dan Investasi Logam Mulia Dalam Meningkatkan Profitabilitas - Mulyana Machmud (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2021)
This research aims to find out the development of Safe Fast Credit (KCA) and Precious Metals Investment to improve profitability in 2017-2019. The analysis method used in this study is to use the profitability formula (net profit margin on sales, return on investment and return on equity).The Research results, show that net profit on sales in Safe Fast Credit (KCA) in 2017-2019 obtained a percentage yield of 32% and already met the standards industry/company measurement average while the distribution of Precious Metals in 2017-2019 obtained a percentage yield of 27% and already met the average industry/company measurement standards.Return on investment in 2017-2019 obtained a percentage yield of 59% and already met the industry/company measurement average standards.Return on equity in 2017-2019 obtained a percentage yield of 56% and already met the industry/company measurement average standards.From the three indicators the ratio are seen that the result can increase profit.